Smoking behavior among adolescents in Thailand and Malaysia - Tawima Sirirassamee (2018)
The objective of this study was to examine the smoking behavior among adolescents in Thailand and Malaysia. Population-based, national surveys were conducted among 1,704 adolescents between the ages of 13 and 18 from Thailand (n = 927) and Malaysia (n = 777). Respondents were selected using multistage cluster sampling. Respondents were asked to complete self-administered questionnaires. Approximately 5% of Thai and Malaysian adolescents were current smokers, while an additional 8.6% of Thai and 8.1% of Malaysian adolescents reported being beginning smokers. On average, Thai smokers reported first smoking a whole cigarette at 14.6 years old (SD = 1.9), while Malaysian smokers at age 13.9 years (SD = 2.2). More than half of Thai smokers (60.4%) reported they bought cigarettes themselves and 29.9% got cigarettes from friends. In Malaysia, most smokers (68.3%) reported they bought cigarettes themselves, only 20.7% got cigarettes from friends. Seventy-six percent of Thai adolescent smokers smoked factory-made brands as their usual brand compared to 27.7% of Malaysian adolescent smokers. Eight percent of Thai adolescents and 10% of Malaysian adolescents reported smoking hand-rolled cigarettes. Approximately half of Thais and more than 40% of Malaysian smokers reported they tried to quit smoking within the past month. The smoking prevalence of Thai adolescents is close to that of Malaysian adolescents. Factory-made cigarette consumption is an important problem in Thai adolescents and needs to be targeted.